АРИСТОКРАТИЯ, МЕРИТОКРАТИЯ И ПЕРМАНЕНТНАЯ ПРИРОДА УТОПИЗМА - Вандышев, В. Н. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
Рассмотрены особенности трансформации идеологии утопизма в различных исторических условиях и показано, что на протяжении многих столетий утопизм непреодолим ни как концепт, ни как литературный жанр. Утопизм рассмотрен также в контексте анализа природы и сущности знания вообще, его доступности и восприятия в различные периоды истории. С плюрализацией средств массовой информации, с ростом рекламной индустрии, обращенной к обширной аудитории, средства массовой информации зажили своей собственной жизнью, формируя основание для новой властной структуры информационного общества – нетократии. Последняя и становится одной из новейших форм утопизма. Вандишев В.М. Аристократія, меритократія та перманентна природа утопізму. Розглянуто особливості трансформації ідеології утопізму в різних історичних умовах і показано, що впродовж багатьох сторіч утопізм непереборний ні як концепт, ні як літературний жанр. Утопізм розглянутий також в контексті аналізу природи і суті знання взагалі, його доступності і сприйняття в різні періоди історії. З плюралізацією засобів масової інформації, із зростанням рекламної індустрії, зверненої до широкої аудиторії, засоби масової інформації зажили своїм власним життям, формуючи підставу для нової владної структури інформаційного суспільства – нетократії. Остання і стає однією з новітніх форм утопізму. Ключові слова: утопізм, аристократія, меритократія, комунікація, плюралізм, нетократія, медіа, інформація. Vandyshev V.N. Aristocracy, meritokracy and permanent nature of utopizm. The features of transformation of ideology of utopizm are considered in different historical terms and it is retuned that during many centuries utopizm is insurmountable neither as concept nor as a literary genre. Utopizm is considered also in the context of analysis of nature and essence of knowledge in general, his availability and perception in different periods of history. From pluralism mass medias, with growth of publicity industry, turned to the vast audience, mass medias began to live the own life, forming foundation for the new imperious structure of informative society – netokracy. The last becomes one of the newest forms of utopizm. Keywords: utopizm, aristocracy, meritokracy, communication, pluralism, netokracy, media, information.